TALABALARDÍŃ MATEMATIKALÍQ ANALIZ KURSÍN ÚYRENIWDEGI ÓZBETINSHE JUMÍSÍ - Jańabergenova, A. (SCIENCE and SOCIETY, 2019)
The article is devoted to the courses of mathematical analysis studied in the independent work of students of higher educational institutions.